The Modern Concept of Development of Vaccine Prevention in Russia - N. I. Briko; I. V. Feldblyum (Эпидемиология и вакцинопрофилактика, 2019)
This paper reviews concept issues of vaccination in Russian Federation. There are three periods of vaccination history. The provisions of the concept were formulated on the basis of the results of multi-year researches and analysis of data from domestic and foreign studies. Main provisions aim at: reconstruction of domestic vaccine production; improvement of the national immunization schedule and public policy for country biosafety; promotion of the WHO strategy for full immunization throughout life in Russia; development of the national immunization schedule for adults and monitoring system for adverse events following immunization; implementation of vaccination risk management and epidemiological surveillance for disease prevention, improvement of vaccination compliance among people, health care workers, mass media, legislative and executive authorities. Implementation of the provisions of the modern vaccination concept in Russia would contribute to solving demographic problems, to reduce morbidity and mortality, to promote active aging, and would have a significant economic effect.